2015
DOI: 10.1002/pd.4640
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of subchromosomal events detected by whole‐genome noninvasive prenatal testing

Abstract: ObjectiveA novel algorithm to identify fetal microdeletion events in maternal plasma has been developed and used in clinical laboratory‐based noninvasive prenatal testing. We used this approach to identify the subchromosomal events 5pdel, 22q11del, 15qdel, 1p36del, 4pdel, 11qdel, and 8qdel in routine testing. We describe the clinical outcomes of those samples identified with these subchromosomal events.MethodsBlood samples from high‐risk pregnant women submitted for noninvasive prenatal testing were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 28 publications
5
140
1
2
Order By: Relevance
“…In such cases, decisions on informing and advising couples were taken after multidisciplinary discussions between lab specialists, clinical geneticists and maternal–fetal medicine specialists. NIPT data on the occurrence of these anomalies in a population with an increased risk based on the FCT are slowly emerging 31, 32. In our study, 31% of the chromosomal abnormalities found were other than trisomy 21, 13 or 18.…”
Section: Discussionsupporting
confidence: 45%
“…In such cases, decisions on informing and advising couples were taken after multidisciplinary discussions between lab specialists, clinical geneticists and maternal–fetal medicine specialists. NIPT data on the occurrence of these anomalies in a population with an increased risk based on the FCT are slowly emerging 31, 32. In our study, 31% of the chromosomal abnormalities found were other than trisomy 21, 13 or 18.…”
Section: Discussionsupporting
confidence: 45%
“…6 Recently, select microdeletion syndromes and smaller copy-number changes, as well as other autosomal aneuploidies, have been added by some laboratories as additional screening options. 7,8 Various factors affect the accuracy of NIPS results, including confined Disclaimer: ACMG Clinical Laboratory Practice Resources are developed primarily as an educational tool for clinical laboratory geneticists to help them provide quality clinical laboratory genetic services. Adherence to these practice resources is voluntary and does not necessarily assure a successful medical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Only one other commercial provider has published its experience with microdeletion screening 7 , while another presented data at the most recent meeting of the International Society for Prenatal Diagnosis 8 (Table 1). It is disappointing that, despite a combined total of more than 200 000 women undergoing microdeletion screening in these three studies, we still lack the basic performance metrics of sensitivity and negative predictive value for 22q11.2 DS in clinical practice.…”
Section: Other Studies On 22q112 Ds Screeningmentioning
confidence: 99%
“…In this present study, only two maternal carriers were suspected (one confirmed with genetic testing, and the other suspected on clinical findings). In another recent study that used a random whole-genome sequencing method, 20 of 32 high-risk calls involved a suspected maternal component 7 . These unexpected maternal findings clearly pose ethical implications if widespread screening in the low-risk population is to be considered seriously.…”
Section: Criteria For Screening For a Health Conditionmentioning
confidence: 99%